Research on a Simplified Model of an Aluminum Vapor Chamber in a Heat Dissipation System - Shuang Han; Lixin Yang; Zihao Tian; Xiaofei Yuan; Hongyan Lu (Entropy, 2019)
With the rapid increase of power densities of electronic components, the traditional heat dissipation method of air forced convection has reached a heat transfer limit. As efficient phase change heat exchangers, vapor chambers have become an important guarantee for the development of high-power electronic components. Aluminum vapor chambers have become the future development trend because they are more lightweight and less expensive. In order to study the suitable simplified model of the aluminum vapor chamber in the radiating system, the testing system is established to test the thermal characteristics of the vapor chamber. First, six simplified models of the vapor chamber are proposed. Then, the thermal characteristics of the simplified models are simulated by STAR CCM+ software. Next, the error of the thermal resistance of the simplified model and the real vapor chamber is analyzed. Finally, a most suitable simplified model is obtained in the cooling system.